The Role of Parents in Reducing Stunting Cases in Pregnant Women ( Study in Semenok Village, Mandor District, Landak Regency ) - Ily, Wiwiana; Mukhlis, Mukhlis; Rupita, Rupita; Sudirman, Sudirman; Musa, Pabali (International Journal of Education, Vocational and Social Science, 2024)
Stunting is one of the main health problems faced by many developing countries, including Indonesia. The role of parents is crucial in efforts to reduce stunting rates through various approaches that include preventive, curative, promotive, and rehabilitative roles. This study examines how these roles can be implemented effectively to prevent and treat stunting in children. This study uses a descriptive qualitative method, the informants consist of representatives of pregnant women, health center officers and Semenok Village Posyandu. The results of the study show that there are several roles, including a preventive role carried out by ensuring adequate nutritional intake during pregnancy and early childhood life, as well as regular pregnancy check-ups. The curative role focuses on handling when stunting symptoms begin to appear, involving cooperation between parents and health workers in providing appropriate nutritional care and consultation. The role of promotive, parents play an active role in disseminating information related to stunting prevention through education and counseling programs. This increase in knowledge promotes better parenting and optimal nutrition fulfillment. Meanwhile, the rehabilitative role aims to restore the condition of children who have experienced stunting through nutritional interventions and sustainable mental stimulation. The conclusion of the combination of these four roles provides opportunities for parents to contribute significantly to reducing stunting rates. With a comprehensive approach and adequate support, it is hoped that the stunting rate can be reduced, so that children can grow healthy and reach their optimal potential.